Public administration in an atypical transition and the need for the agents of europeanisation in Kosovo - Istrefi, Remzije (Array, 2020)
This article investigates public administration reform in Kosovo by: a) analysing the extent to which an atypical transition affects administrative and governance reforms, b) examining the Europeanisation process and efforts to harmonise legislation with the European Union’s acquis communautaire as the main driving force towards a successful transition, and c) reiterating the relevance and function of the educational system in the Europeanisation process. The article addresses the following question: can the Europeanisation process be accomplished successfully when the educational system, which is limited in scale, doesnot manage to generate a sufficient number of Europeanisation agents? In post1999 Kosovo, public administration has been undergoing continuous reforms to detach itself from the discriminatory legacy of communist and Serbian rule, to transfer authorities from internationally established bodies to local ones, toenhance capacity-building through international assistance, and to move forward with further reforms as part of Kosovo’s EU integration efforts. Public administration reforms remain affected by past legacies, namely the atypical transition characterised by a post-WWII communist dictatorship, the Serbianapartheid-like discrimination in the 1990s, an UN-led interim administration, and challenges of capacity-building. The article concludes that without a fully consolidated and crisis-resistant democracy neither the initiated public administration reform based on the values of good governance, nor the “fair and just”distribution of resources in society have a perspective. For instance, to comply successfully with the public administration reform obligations set out in the EU’s Stabilisation and Association Agreement, Kosovo needs greater capacities and professionals serving as Europeanisation agents. As a result, much larger investments in education, research, and development appear to be paramount.